2018
DOI: 10.1002/uog.18929
|View full text |Cite
|
Sign up to set email alerts
|

Added value of chromosomal microarray analysis over karyotyping in early pregnancy loss: systematic review and meta‐analysis

Abstract: In comparison with conventional karyotyping, CMA provides a significant increase in test success rate and incremental diagnostic yield in early pregnancy loss. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 42 publications
8
55
2
Order By: Relevance
“…While only a few studies have reported the added value of CMA over conventional karyotyping in stillbirth, there have been many reported series in miscarriage. That review included 5507 early gestational losses from 23 studies, and demonstrated a 27% increase in test success rate of CMA over karyotyping (68% to 95%), a value greater than the increased success rate observed in the current meta‐analysis (75% to 90%). Although a statistical comparison is not possible, the fact that the observed rate of informative results of CMA in stillbirth was slightly higher compared with that in miscarriage (95% vs 90%), while the reverse was true for karyotyping (68% vs 75%), appears to be of limited clinical relevance.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…While only a few studies have reported the added value of CMA over conventional karyotyping in stillbirth, there have been many reported series in miscarriage. That review included 5507 early gestational losses from 23 studies, and demonstrated a 27% increase in test success rate of CMA over karyotyping (68% to 95%), a value greater than the increased success rate observed in the current meta‐analysis (75% to 90%). Although a statistical comparison is not possible, the fact that the observed rate of informative results of CMA in stillbirth was slightly higher compared with that in miscarriage (95% vs 90%), while the reverse was true for karyotyping (68% vs 75%), appears to be of limited clinical relevance.…”
Section: Discussionmentioning
confidence: 76%
“…Our group recently reported an analogous systematic review and meta‐analysis on the added value of CMA over karyotyping in gestational loss < 20 weeks of gestation. While only a few studies have reported the added value of CMA over conventional karyotyping in stillbirth, there have been many reported series in miscarriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason that karyotyping the products of conception is usually discouraged is the low success rate and high risk of maternal contamination. A recent meta‐analysis quoted a success rate for karyotyping of 68% in reported series, and maternal cell contamination has been shown to account for 22% of samples on average. In our center, we offer routinely chorionic villus sampling before evacuation of the uterus, with analysis by both short‐ and long‐term cultures.…”
Section: Initially Targeting Down Syndrome and Spina Bifidamentioning
confidence: 99%
“…At present, the advantages of CMA in PND are gradually presented with the rapid development of chip technology. CMA has the ability to disclose a wide range of chromosomal abnormalities with length from 50 kb to 100 kb, which produces 100 times better resolution than karyotyping [11]. More and more evidence has indicated that CMA can improve the diagnostic accuracy by approximately 15-20% over that of karyotyping when applied for the evaluation of fetuses with unexplained developmental delay, mental retardation, and autism [12].…”
Section: Introductionmentioning
confidence: 99%